2021
DOI: 10.2478/raon-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

TIPS vs. endoscopic treatment for prevention of recurrent variceal bleeding: a long-term follow-up of 126 patients

Abstract: Background Recurrent bleeding from gastroesophageal varices is the most common life-threatening complication of portal hypertension. According to guidelines, transjugular intrahepatic portosystemic shunt (TIPS) should not be used as a first-line treatment and should be limited to those bleedings which are refractory to pharmacologic and endoscopic treatment (ET). To our knowledge, long-term studies evaluating the role of elective TIPS in comparison to ET in patients with recurrent variceal bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…For secondary prophylaxis of variceal bleeding in cirrhosis, the combination of NSBBs with VBL seems more efficient in preventing re-bleeding compared with VBL alone 714–716 . TIPSS seems more effective than VBL in preventing re-bleeding in patients who first bleed while on beta-blockers, those with contraindications to beta-blockers or with refractory ascites, and in patients with fundal varices 696,697,714,717,718 . TIPSS seems more effective than VBL with propranolol in preventing recurrent oesophageal variceal bleeding in patients with advanced cirrhosis and portal vein thrombosis or with high hepatic venous pressure gradient 719,720 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For secondary prophylaxis of variceal bleeding in cirrhosis, the combination of NSBBs with VBL seems more efficient in preventing re-bleeding compared with VBL alone 714–716 . TIPSS seems more effective than VBL in preventing re-bleeding in patients who first bleed while on beta-blockers, those with contraindications to beta-blockers or with refractory ascites, and in patients with fundal varices 696,697,714,717,718 . TIPSS seems more effective than VBL with propranolol in preventing recurrent oesophageal variceal bleeding in patients with advanced cirrhosis and portal vein thrombosis or with high hepatic venous pressure gradient 719,720 .…”
Section: Discussionmentioning
confidence: 99%
“…714 -716 TIPSS seems more effective than VBL in preventing re-bleeding in patients who first bleed while on beta-blockers, those with contraindications to betablockers or with refractory ascites, and in patients with fundal varices. 696,697,714,717,718 TIPSS seems more effective than VBL with propranolol in preventing recurrent oesophageal variceal bleeding in patients with advanced cirrhosis and portal vein thrombosis or with high hepatic venous pressure gradient. 719,720 According to recent systematic reviews and network meta-analysis, TIPSS may result in a larger decrease in symptomatic rebleeding than VBL, or VBL combined with NSBBs, whereas VBL is associated with fewer SAEs than sclerotherapy.…”
Section: Variceal Bleedingmentioning
confidence: 99%
“…Interventional treatment: There are currently two main procedures: transjugular intrahepatic portosystemic shunt (TIPS) and percutaneous transhepatic variceal embolization (PTVE). Studies have shown that TIPS is highly effective in stopping hemorrhage in cases of acute bleeding [ 9 ]. However, previous studies have concluded that TIPS can have a negative impact on the long-term prognosis of patients after the procedure and that TIPS is a difficult procedure to perform, making it difficult to generalise in the context of a large hepatitis population in China.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study was conducted on 126 hemodynamically stable, nonbleeding patients (last bleed: mean 35 days) who had experienced recurrent episodes of variceal bleeding. 39 When the TIPS group was compared with the endoscopic therapy group, recurrence of variceal bleeding was significantly less for patients undergoing TIPS placement (66.1 vs. 21.4%, p < 0.001), and endoscopic therapy was the only significant independent predictor of recurrent bleeding (OR: 7, 95% CI: 3.0–16.5, p < 0.001). Cumulative survival rates between the two groups were similar, but the incidence of death secondary to variceal bleeding was lower for the TIPS group (10 vs. 28.6%).…”
Section: Gastroesophageal Varices Without a Splenorenal Shuntmentioning
confidence: 95%